Growth response of zinc as nano-fertilizer in tomato(Solanum lycopersicum L.) and sweet pepper (Capsicum annuum L.) - Bhardwaj, G; Brar, P S; Chauhan, A; Sharma, J C (Journal of Horticultural Sciences, 2025)
The study was carried out to determine ideal zinc concentration for its use as nano-fertilizer, through application of zinc oxide (ZnO) nanoparticles in tomato and sweet pepper. Two years pot experiment was carried out in completely randomized design, comprised of seven treatments with three replications. ZnO nanoparticles were applied as seed treatment [T2 (50 mg/L), T4 (100 mg/L), and T6 (150 mg/L)] and foliar application [T3 (50 mg/L), T5 (100 mg/L), and T7 (150 mg/L)], respectively, and control with no nanoparticles application. Results revealed that plant height, root length, number of primary branches, plant biomass, yield, and nutrient uptake of tomato and sweet pepper showed the highest significant response to ZnO nanoparticles (50 mg/L) applied through foliar application. On the other hand, seed treatment of ZnO nanoparticles (50 mg/L) registered significant higher nutrient content. Study concluded that 50 mg/L was ideal concentration of ZnO nanoparticles that proved to be effective in enhancing sustainability by improving growth, yield, nutrient content and uptake of tomato and sweet pepper.